Mapping Properties For Conic Regions Associated With Rabotnov Functions - Muhammad Amin; Sabihee Anwaar; Saima Mushtaq; Barya Iftikhar; Haidar Ali (Spectrum of Engineering Sciences, 2025)
Keywords: Analytic Function, Univakent Function, Statlike function, Convex Function, Uniformly Convex.